Lung function measurements in the Greenlandic Inuit population: results from the Greenlandic health survey 2017–2019 - P. Geisler; M. E. Jørgensen; C. Viskum Larsen; P. Bjerregaard; V. Backer; A. S. Homøe; I. Olesen; U. M. Weinreich (European Clinical Respiratory Journal)
Background Little is known about lung function in Inuit. The aim of this study was to describe lung function and the prevalence of obstructive and restrictive lung disease among Inuit in GreenlandMethods During the 2017–2019 Health Survey, spirometry, with forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), and FEV1/FVC ratio in liters (L), and percent of predicted value (pred%) were recorded according to Global Lung function Initiative standard reference values (GLI). Smoking history was obtained. Obstructive spirometry was defined as FEV1/FVC <70%. Restrictive spirometry was proposed by FVC < 80% and FEV1/FVC >90%.Results Based on validated spirometries, 795/2084 persons were included in this cross-sectional, descriptive study. Of those, 54.6% were current- and 27.7% former smokers. In Inuit, normal lung function was higher than predicted GLI (FEV1 107.2 pred%/FVC 113.5 pred%). In total, 106 (13.3%) were found to have an obstructive lung function measurement and 11 (1.4%) had a restrictive pattern. Among current smokers, the prevalence of obstructive lung function was 16.4%. An accelerated decline in lung function was observed > 50 years old (y.o), compared to <50 y.o.Conclusion This study indicates that Inuit has higher absolute lung function values than standard GLI, despite the large proportion of smokers, which indicate a need for Inuit reference values in the daily clinical praxis. The high prevalence of obstructive lung function and rapid decline in lung function indicates the need for fucus on health issues that may affect lung health in Greenland.